Comorbid insomnia and sleep apnoea is associated with all-cause mortality. Issue 1 (14th July 2022) - Lechat, Bastien; Appleton, Sarah; Melaku, Yohannes Adama; Hansen, Kristy; McEvoy, R. Doug; Adams, Robert; Catcheside, Peter; Lack, Leon; Eckert, Danny J.; Sweetman, Alexander
Background: Increased mortality has been reported in people with insomnia and in those with obstructive sleep apnoea (OSA). However, these conditions commonly co-occur and the combined effect of comorbid insomnia and sleep apnoea (COMISA) on mortality risk is unknown. This study used Sleep Heart Health Study (SHHS) data to assess associations between COMISA and all-cause mortality risk. Methods: Insomnia was defined as difficulties falling asleep, maintaining sleep and/or early morning awakenings from sleep ≥16 times per month, and daytime impairments. OSA was defined as an apnoea–hypopnoea index ≥15 events·h −1 . COMISA was defined if both conditions were present. Multivariable adjusted Cox proportional hazards models were used to determine the association between COMISA and all-cause mortality (n=1210) over 15 years of follow-up. Results: 5236 participants were included. 2708 (52%) did not have insomnia/OSA (reference group), 170 (3%) had insomnia-alone, 2221 (42%) had OSA-alone and 137 (3%) had COMISA. COMISA participants had a higher prevalence of hypertension (OR 2.00, 95% CI 1.39–2.90) and cardiovascular disease (CVD) (OR 1.70, 95% CI 1.11–2.61) compared with the reference group. Insomnia-alone and OSA-alone were associated with higher risk of hypertension but not CVD compared with the reference group. Compared with the reference group, COMISA was associated with a 47% (hazard ratio 1.47, 95% CI 1.06–2.07) increased risk of mortality. The association between COMISA and mortality was consistent across multiple definitions of OSA and insomnia. Conclusions: COMISA was associated with higher rates of hypertension and CVD at baseline, and an increased risk of all-cause mortality compared with no insomnia/OSA. Comorbid insomnia and sleep apnoea is associated with a 47% increase in mortality risk compared with participants with no insomnia or obstructive sleep apnoea over 15 years of follow-up https://bit.ly/3kXylQH